Application of integrated drilling and stamping technology in gas extraction through layer drilling. Issue 4 (July 2022) - Song, Jinxing; Zhang, Huiyan; Yu, Shiyao; Su, Xianbo
In coal mine gas extraction in China, the current hydraulic permeability enhancement measures generally have complex processes, low adaptability, long operation time, and high labor intensity. This makes it challenging to meet the requirements of coal mining enterprises for safe and efficient mining, and there is an urgent need to develop new technologies to enhance gas extraction and production. This paper proposed an integrated drilling and stamping technology to enhance gas extraction and production and integrates drilling, hydraulic jet fracturing, and hydraulic punching to enhance the permeability of coal seams. A field test was conducted using the specially-developed integrated drilling and stamping equipment to extract gas from the 16101 bottom pumping lane penetration hole in the Jiulishan Mine, Jiaozuo, Henan. The test results show that compared with the hydraulic punching technology previously used in the mine, the punching time of the soft coal seam was shortened by 66–75%, the coal output was increased by 1.7 times, and the punching hole aperture was increased by 1.3 times. Hydraulic injection fracturing was successfully performed to increase the permeability of the hard coal seams, and the fracturing formed a shot hole depth of 345–539 mm. After the integrated drilling and stamping of the drill holes, the coal output, gas extraction concentration, pure gas extraction volume, and coal seam permeability coefficient increased by 2.4, 2.2, 4, and 37.3 times, respectively. The gas flow decay coefficient of the drills holes was also further reduced, which significantly improved the extractionefficiency. Thus the integrated drilling and stamping technology can transform the process of gas extraction from regular extraction to quick, economic, pure, and clean extraction. Thus, this technology has large applicable value for underground gas management in coal mines.